Epstein–Barr virus is associated with grey matter atrophy in multiple sclerosis. Issue 6 (23rd January 2009) - Zivadinov, R; Zorzon, M; Weinstock-Guttman, B; Serafin, M; Bosco, A; Bratina, A; Maggiore, C; Grop, A; Tommasi, M A; Srinivasaraghavan, B; Ramanathan, M
Abstract : Objective: The aim of the study was to determine whether the presence of anti-Epstein–Barr virus (EBV) antibodies is associated with MRI measures of brain injury and neurodegeneration in patients with multiple sclerosis (MS). Methods: 135 patients with MS (86 women, 49 men) underwent brain MRI and testing for antibodies against EBV. MRI measurements included gadolinium enhancing lesion volume, T1 and T2 lesion volumes and fractions of whole brain parenchyma (BPF), white matter and grey matter (GMF). The anti-EBV panel included anti-EBV early antigen IgG, anti-EBV nuclear antigen IgG and anti-EBV viral capsid antigen (VCA) IgG levels. The relationships between antibody levels and MRI measurements were assessed in regression analysis. Repeat measurements of anti-EBV VCA IgG and MRI measures were available for a subset of 50 patients after a mean follow-up of 3.1 years. Results: GMF (R 2  = 0.24 for overall model, p = 0.002) and BPF (R 2  = 0.39 for overall model, p<0.001) showed negative associations with anti-EBV-VCA IgG levels. A greater decline in BPF over 3 years was significantly associated with increased 3 years prior time point anti-EBV VCA IgG levels (p<0.001). Conclusions: The results suggest that the presence of anti-EBV antibodies is associated with MRI markers of GM atrophy in MS and with increased loss of brain volume over 3 years.